Li+ concentration and morphological changes at the anode and cathode interphases inside solid-state lithium metal batteries - Chun Huang; Matthew D Wilson; Ben Cline; Abeiram Sivarajah; Wiebe Stolp; Matthieu N Boone; Thomas Connolley; Chu Lun Alex Leung (JPhys Energy)
Irregular Li heterostructure growth at the interphase between the solid electrolyte and anode reduces solid-state Li metal battery (SSLMB) performance, but the fundamental cause is still elusive. Measuring and imaging Li ^+ ion diffusion in operando inside an SSLMB using a commercially standard cell configuration are extremely challenging because the ultra-light Li element exhibits a minute signal-to-noise ratio using most x-ray-related characterization methods, and the weak x-ray signals of Li ^+ are buried by strong signals of other heavy transition metal elements in the cathode and battery enclosure. Here, we pioneer novel operando correlative imaging of coupling x-ray Compton scattering with computed tomography (XCS-CT), which is able to quantify the interplay between spatially resolved Li ^+ ion diffusion kinetics and Li ^0 metal structure growth at the interphases of both the anode and cathode sides inside a full-cell SSLMB using a solid polymer electrolyte (SPE) and commercially standard cell configuration during (dis)charging. We show a 61% increase in the efficiency of extracting Li ^+ ions from the cathode LiNi _0.6 Mn _0.2 Co _0.2 O _2 to the anode during charging at 0.1 C compared with at 1 C due to restricted Li ^+ ion diffusion at the higher rate inside SSLMB. However, this led to the formation of a more irregular interfacial morphology, consisting not only of Li ^0 dendrites, but also sub-surface pore formation at the anode/SPE interphase. We find that surprisingly, the irregular Li ^0 structure initiation and growth are accelerated during the first Li stripping step, not the Li plating step, and the root cause is the onset imbalance of Li ^+ ion diffusion and redox reactions between the anode and cathode. These insights highlight the benefits of asymmetric charging and discharging rates as a promising solution to improving SSLMB performance with SPEs. The operando correlative XCS-CT imaging technique has the potential to study the relationship between active ion concentrations and buried morphological changes for a variety of battery chemistries.